Teacher Motivation and Commitment through Transformational Leadership in China’s Vocational Schools - Liu, Pinxi; Alias , Bity Salwana; Mansors , Azlin Norhaini (Journal of Ecohumanism, 2024)
Aim: The goal of this literature review was to look into and rate the roles of transformational leadership in Chinese vocational schools, as well as how these roles affect teachers' motivation and commitment. Methodology: An organized search was done using trustworthy academic sources like ERIC, Education Research Complete, PsycINFO, Google Scholar, Taylor & Francis, and Emerald for this literature review. The purpose of choosing these databases was to make sure that the available literature was looked at in its entirety. Precisely chosen keywords and phrases related to transformational leadership, educator commitment and motivation were used in the search strategy.Results and conclusions: According to the review, the primary factors that make teachers in vocational schools motivated, committed, and good at their jobs are program development, mentorship, and inventive methods of teaching. Transformational leadership is important for inspiring people because it focuses on support, change, and intellectual growth. Leadership styles encourage creative and collaborative learning environments that are good for teachers. Recommendations: To make Chinese vocational schools better places to learn, it is recommended that funding for the development of transformational leadership tonsure teachers have access to basic tools should be given more attention. To get teachers more committed and motivated, you have to deal with resistance to change and draw attention to the benefits of these leadership styles. Practical Implications: The findings from this review have practical implications for educators, administrators, and policymakers, as they highlight the significance of leadership in shaping the educational experiences.